2016
DOI: 10.1007/s11102-016-0767-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of prolactinomas: a survey of physicians from the Middle East and North Africa

Abstract: This is the first study of the clinical management of prolactinomas in the MENA region. Some of the practices are not in line with the latest Endocrine and Pituitary Societies guidelines. These warrant further discussions of contemporary guidelines in regional forums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Beshyah et al [31] conducted a survey on the management of prolactinomas by physicians from the Middle East and North Africa. Some of the practices are not in line with the latest Endocrine and Pituitary Societies guidelines.…”
Section: What Are the Current Trends In The Management Of Prolactinommentioning
confidence: 99%
See 1 more Smart Citation
“…Beshyah et al [31] conducted a survey on the management of prolactinomas by physicians from the Middle East and North Africa. Some of the practices are not in line with the latest Endocrine and Pituitary Societies guidelines.…”
Section: What Are the Current Trends In The Management Of Prolactinommentioning
confidence: 99%
“…65 % and 38 % respectively of respondents advocated discontinuation of treatment with dopamine agonists for patients with microprolactinomas and macroprolactinomas. Finally, 48 % would allow breast-feeding without restriction, 28 % would restrict it to patients with microprolactinomas and 25 % would not recommend it for women with prolactinomas [31].…”
Section: What Are the Current Trends In The Management Of Prolactinommentioning
confidence: 99%
“… The data of Brazil and MENA are derived from Ref. ( 4 , 5 ) respectively. P values using the Chi-square test (or Fisher’s exact test).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the current clinical practice, there are still controversies concerning appropriate diagnosis and treatment of prolactinoma, such as the identification of hyperprolactinemia, the choice of treatment methods, the duration of drug treatment and management of pregnancy and breastfeeding. In recent years, two studies have conducted questionnaire surveys of clinicians’ management of prolactinomas reflecting self-reported clinical diagnoses and treatment ( 4 , 5 ). However, no similar data are available from China.…”
Section: Introductionmentioning
confidence: 99%
“…Opinions on the infl uence of breastfeeding in the case of a pre-existing prolactinoma are divided. A survey of 468 doctors showed that 47% of them would allow unrestricted breastfeeding, 28% would allow breastfeeding only by patients with microprolactinomas and 25% would not recommend breastfeeding at all 37 .…”
Section: Prolactinomamentioning
confidence: 99%